Eine Titeldivergenz in den Grabräuberpapyri: Ein möglicher Beleg für Amtsenthebung als Strafe - Böhm, Billy (Zeitschrift für ägyptische Sprache und Altertumskunde, 2024)
In papyrus Amherst 6 + Léopold II (16 th regnal year of Ramesses IX) of the so-called Tomb Robbery Papyri, a certain Amenemheb is mentioned three times among a number of other individuals. He was convicted of robbing the tombs of western Thebes. In this context, the titles attributed to him on the papyrus are of particular interest. In 2:2 and 3:13, he is referred to as “cultivator of the temple of Amenope” ( ꜥḥ.wtj n(.j) pr Jmn-jp.t ), whereas, in 4:6 he is called “agent of the temple of Amenope” ( rwḏ.w Jmn-m-ḥb n(.j) pr Jmn-jp.t ). Based on a detailed analysis of the contents of Papyrus Amherst 6 + Léopold II, this article demonstrates that the reason for this difference is ouster. This means that Amenemheb at least formally lost his office – unlike his colleagues. Afterwards, he was sentenced to death, which is not mentioned explicitly in the text but which we may assume with some certainty. If this is correct, this is one of the few examples of ouster as a punishment being carried out in reality. However, it was not targeted primarily at the denial of the delinquent’s access to the assets, which were tied to it.